Efeito inibitório do anetol sobre a resposta inflamatória aguda - Domiciano, Talita Perdigão (2011)
Anethole (1-methoxy-4-(1 prophenyl) benzene) occurs naturally as a major component of star anise (Illicium verum) essential oil, accounting for more than 90% of volatile components. It is widely used as a flavoring substance in bakery products, sweets and beverages. It presents a variety of pharmacological activities such as antioxidant, fungicid, bactericid and insecticid actions. The objective of this study was to evaluate the anti-inflammatory activity of anethole in acute experimental inflammatory response. We used the models of croton oil-induced ear edema and carrageenan-induced pleurisy. The investigated parameters were edema formation, leukocyte migration and inflammatory mediator evaluation. Treatment with anethole reduced the volume of pleural inflammatory exudate, with doses of 250 and 500 mg/kg similarly reducing the response intensity and number of leukocytes. There was a reduction in the levels of NO and PGE2 in the inflammatory exudate, but levels of TNF-α and IL-1β were not changed. In ear edema, the treatment with anethole was able to inhibit the formation of edema when administered orally, but not when administered topically. Altogether, the results indicate that the anti-inflammatory effect of anethole may be related to an inhibitory action on production and/or release of PGE2 and NO.